1998
DOI: 10.1007/s002210050383
|View full text |Cite
|
Sign up to set email alerts
|

NOS-like immunoreactive neurons express GABA-like immunoreactivity in rabbit and rat retinae

Abstract: In rabbit and rat retinae, wholemounted preparations and 40 microm thick vibratome sections were processed for nitric oxide synthase (NOS) immunoreactivity and consecutive semithin sections were immunostained with anti-NOS and anti-GABA antisera, respectively. Two types of NOS-labelled amacrine cells were identified: type 1 cells with larger somata were intensely stained, and type 2 cells with smaller somata were weakly stained. A few displaced amacrine cells also showed NOS-like immunoreactivity. All these NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
6
22
2
Order By: Relevance
“…This assumption has been corroborated by the fact that NADPH-d is colocalized with NOS in several neuronal systems Perez et al, 1995) and also by the fact that an NADPH-d reaction is not detected in the retinae of mice devoid of the neuronal NOS gene (Darius et al, 1995). Thus, NADPH-d histochemistry (Sandell, 1985;Sagar, 1986Sagar, , 1990M眉 ller et al, 1988;Cobcroft et al, 1989;Mitrofanis, 1989;Osborne et al, 1993;Lau et al, 1994) and immunocytochemical methods using anti-NOS antisera Koistinaho et al, 1993;Yamamoto et al, 1993;Oh et al, 1998Oh et al, , 1999Chun et al, 1999;Kim et al, 1999) have been applied to study the morphology and topographical distribution of NOS cells in the mammalian retina.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This assumption has been corroborated by the fact that NADPH-d is colocalized with NOS in several neuronal systems Perez et al, 1995) and also by the fact that an NADPH-d reaction is not detected in the retinae of mice devoid of the neuronal NOS gene (Darius et al, 1995). Thus, NADPH-d histochemistry (Sandell, 1985;Sagar, 1986Sagar, , 1990M眉 ller et al, 1988;Cobcroft et al, 1989;Mitrofanis, 1989;Osborne et al, 1993;Lau et al, 1994) and immunocytochemical methods using anti-NOS antisera Koistinaho et al, 1993;Yamamoto et al, 1993;Oh et al, 1998Oh et al, , 1999Chun et al, 1999;Kim et al, 1999) have been applied to study the morphology and topographical distribution of NOS cells in the mammalian retina.…”
Section: Introductionmentioning
confidence: 89%
“…No colocalization of nNOS and VIP immunoreactivity was observed in the rat retina (Perez et al, 1995). Using double-labeling techniques, the colocalization of NADPH-d or NOS and GABA has been studied in the cat, rat, and rabbit retinae (M眉 ller et al, 1988;Vaney and Young, 1988;Oh et al, 1998;see Fig. 6).…”
Section: Colocalization With Othermentioning
confidence: 95%
“…Several somata (arrowheads) of displaced amacrine cells are visible. Bar 50 碌m toreceptor cells in the rat retina, whereas no NOS immunoreactivity has been observed in these cells in the bovine, rabbit, and rat retinae (Yamamoto et al 1993;Perez et al 1995;Gotzes et al 1998;Oh et al 1998;Chun et al 1999). Accordingly, NO-containing cells might vary from one species to another, or NO-regulated mechanisms in the retina might be more complex.…”
Section: Introductionmentioning
confidence: 84%
“…NADPH-d histochemistry (Sandell 1985;Sagar 1986Sagar , 1990M眉ller et al 1988;Cobcroft et al 1989;Mitrofanis 1989;Osborne et al 1993;Lau et al 1994) and immunocytochemical methods with anti-NOS antisera Koistinaho et al 1993;Yamamoto et al 1993;Oh et al 1998;Chun et al 1999) have been applied to study the morphology and topographical distribution of NOS cells in the mammalian retina. According to the results obtained so far, certain types of amacrine cells and some displaced amacrine cells are consistently labeled.…”
Section: Introductionmentioning
confidence: 99%
“…In the mammalian retina, most retinal neurons containing NOS are presumed to be amacrine cells, although there is considerable variation [Perez et al, 1995;Oh et al, 1998;Kim et al, 1999;Chun et al, 1999]. In the rat retina, studies using NADPH-diaphorase (NADPH-d) histochemistry [Mitrofanis, 1989] and immunocytochemistry using anti-NOS antisera [Patel et al, 1997;Kim et al, 2000] have shown that putative NO-synthesizing cells first appear at P3 or P5 and that these cells are fully developed by the second postnatal week, before the eyes open.…”
Section: Introductionmentioning
confidence: 99%